2022
DOI: 10.1097/pcc.0000000000002979
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Timing of Neurologic Dysfunction Onset Relative to Pediatric Sepsis Recognition*

Abstract: To compare outcomes associated with timing-early versus lateof any neurologic dysfunction during pediatric sepsis.DESIGN: Secondary analysis of a cross-sectional point prevalence study. SETTING:A total of 128 PICUs in 26 countries. PATIENTS:Less than 18 years with severe sepsis on 5 separate days (2013)(2014). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS:Patients were categorized as having either no neurologic dysfunction or neurologic dysfunction (i.e., present at or after sepsis recognition), which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…reflects the full spectrum of acute brain dysfunction during sepsis. The work builds on previous research reported in PCCM (9,10) and helps our field to make progress in studying the problem of neurologic or behavioral changes in sepsis. There is no related editorial but do re-read the two previous commentaries on "sepsis encephalopathy, " which remain relevant today (11,12).…”
mentioning
confidence: 92%
“…reflects the full spectrum of acute brain dysfunction during sepsis. The work builds on previous research reported in PCCM (9,10) and helps our field to make progress in studying the problem of neurologic or behavioral changes in sepsis. There is no related editorial but do re-read the two previous commentaries on "sepsis encephalopathy, " which remain relevant today (11,12).…”
mentioning
confidence: 92%
“…This group reported greatest odds of mortality in the multiple organ dysfunction syndrome phenotype with severe, persistent neurologic dysfunction. All these investigations, including the current report in PCCM (1), used different specific definitions for CNS dysfunction in sepsis, and all described meaningfully increased association with mortality (6). At this point, it is reasonable to infer that the development of any CNS dysfunction in a septic patient, at any point in their illness, should be considered an extremely concerning.…”
mentioning
confidence: 99%
“…This issue of Pediatric Critical Care Medicine (PCCM ) includes an important article describing the relationship between the timing of development of encephalopathy relative to the identification of pediatric sepsis (1). The authors used the existing data set collected for a large, multicenter point prevalence study of pediatric sepsis, the Sepsis Prevalence, Outcomes and Therapies Study (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations